2015
DOI: 10.1016/j.fuproc.2015.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nickel-based catalysts on syngas production from carbon dioxide reforming of waste high density polyethylene

Abstract: Abstract:Syngas production (H 2 and CO) from carbon dioxide reforming of high density polyethylene (HDPE) over Ni-Al catalyst was evaluated in a two-stage fixed bed reactor. Syngas production was favoured by CO 2 addition, with the highest production of 138.81 mmol syngas g -1 HDPE , which was about six times higher than non-catalytic, non-CO 2 addition. The catalytic performances of nickel-based catalysts with different promoter metals (Cu, Mg and Co) in the CO 2 reforming of HDPE were also studied. It was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…For this process, increasing the CO 2 flow rate promoted a higher syngas yield, which rose from 60.7 to 155.0 mmol g −1 [47]. The same CO 2 effect was reported for dry reforming of high density polyethylene (HDPE) over Cu and Mg promoted Ni-Co/Al 2 O 3 catalysts [49]. The authors showed that syngas production increased with CO 2 addition, with 138.81 mmol syngas g −1 HDPE produced under their conditions, which was significantly higher than the amount made with no catalyst and no CO 2 .…”
Section: Waste Processingsupporting
confidence: 65%
See 1 more Smart Citation
“…For this process, increasing the CO 2 flow rate promoted a higher syngas yield, which rose from 60.7 to 155.0 mmol g −1 [47]. The same CO 2 effect was reported for dry reforming of high density polyethylene (HDPE) over Cu and Mg promoted Ni-Co/Al 2 O 3 catalysts [49]. The authors showed that syngas production increased with CO 2 addition, with 138.81 mmol syngas g −1 HDPE produced under their conditions, which was significantly higher than the amount made with no catalyst and no CO 2 .…”
Section: Waste Processingsupporting
confidence: 65%
“…The authors showed that syngas production increased with CO 2 addition, with 138.81 mmol syngas g −1 HDPE produced under their conditions, which was significantly higher than the amount made with no catalyst and no CO 2 . The Ni-Co-Al catalyst exhibited excellent anti-coking performance, which showed an overall very high resistance to catalyst deactivation and the highest CO 2 conversion (57.62%) [49]. …”
Section: Waste Processingmentioning
confidence: 99%
“…The Ni-Co-Al2O3 catalyst used in the experiments was chosen, based on its high activity in terms of syngas production as reported in our previous study [18]. Two types of catalyst preparations methods are investigated; rising-pH and impregnation.…”
Section: Methodsmentioning
confidence: 99%
“…At the catalyst level, many attempts have been performed to control the deposition of coke in these reactions or minimize its impact. Changing the morphology of the metal (Ni) has recurrently been used to control catalyst deactivation, either by decreasing the particle size [254,255], changing the chemical environment of Ni [256], using a different synthetic pathway [257], using different calcination/reduction methods [144], or using other metals such as the incorporation of Co [258,259], the use of Fe-Zn [260] or other metals all together [261]. On the other side, several attempts have been made to control the catalyst deactivation trough support modification, either by changing porosity or metal placement on the support [28], or by using other conventional supports such as ZrO2, SiO2, MgO, TiO2 [262] or unconventional ones [263].…”
Section: Figure 15mentioning
confidence: 99%